Response of Growing Pigs to Diet Physical Form and Allzyme® SSF Supplementation in a Palm Kernel Meal-Based Diet - Akintunde, AO; Omole, CA; Sokunbi, OA; Lawal, TT; Alaba, O (ANIMAL PRODUCTION, 2011)
Abstract. The increasing cost of conventional feeds calls for the unconventional ones. The effect of Allzyme®SSF and diet physical form on performance, haematological and serum biochemical indices of growing pigs fed with palm kernel meal-based diet was determined. Twenty four growing pigs comprising of twelve male and twelve female weighing 8.95±1.01Kg were assigned into four dietary treatment groups involving dry mash diet, wet mash diet, dry mash diet+ Allzyme®SSF and wet mash diet+ Allzyme®SSF in a completely randomized design. After feeding experiment for six weeks, haematological and serum biochemical parameters were determined. Growth performance was observed on a weekly basis for six consecutive weeks. The results showed that the diet physical form and Allzyme®SSF supplementation in a palm kernel meal-based diet did not significantly affect the haematological and serum biochemical parameters; however weight gain and feed conversion ratio were significantly influenced by the diet physical form and Allzyme®SSF supplementation, thus making dry mash diet + Allzyme®SSF the best dietary treatment. The experiment showed that the diet physical form and Allzyme®SSF supplementation in a palm kernel meal-based diet did not have any negative effect on the growing pigs and growth performance was not hindered; therefore palm kernel meal-based diet in wet or dry mash form with or without Allzyme® SSF supplementation could be fed to growing pigs. Key Words: Allzyme® SSF, supplementation, performance, haematology and biochemistry